1999
DOI: 10.1021/bi982467g
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific Weak Actomyosin Interactions:  Relocation of Charged Residues in Subdomain 1 of Actin Does Not Alter Actomyosin Function

Abstract: Yeast actin mutants with relocated charged residues within subdomain 1 were constructed so we could investigate the functional importance of individual clusters of acidic residues in mediating actomyosin weak-binding states in the cross-bridge cycle. Past studies have established a functional role for three distinct pairs of charged residues within this region of yeast actin (D2/E4, D24/D25, and E99/E100); the loss of any one of these pairs resulted in the same impairment in weak actomyosin interaction and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 40 publications
4
16
0
Order By: Relevance
“…These differences are likely a result of the fact that yeast actin has only two acidic residues at its N terminus, compared with four in cardiac actin. In agreement with this interpretation, the motility, V max , K m , as well as average force of E99A/E100A yeast actin were restored to WT values when two additional negative charges were added to the N terminus (30). Thus in yeast actin, four negative charges in subdomain 1 are more important for WT-actin function than their exact location.…”
Section: Discussionsupporting
confidence: 62%
“…These differences are likely a result of the fact that yeast actin has only two acidic residues at its N terminus, compared with four in cardiac actin. In agreement with this interpretation, the motility, V max , K m , as well as average force of E99A/E100A yeast actin were restored to WT values when two additional negative charges were added to the N terminus (30). Thus in yeast actin, four negative charges in subdomain 1 are more important for WT-actin function than their exact location.…”
Section: Discussionsupporting
confidence: 62%
“…The actin partners of the C-terminal lysine residues of loop 2 are likely in subdomain 1 of actin. The effects of removing negative charge from the N terminus, residues 24/25, or residues 99/100 of actin (15,16,36) are similar to the effects of removing two conserved positive charges from loop 2 of myosin. Mutations in either myosin or actin caused a large decrease in actin activation of ATPase activity, a more modest reduction in binding to actin in the presence of ATP, and impairments in motility.…”
Section: Resultsmentioning
confidence: 92%
“…Chimaeras composed of the Dictyostelium myosin-II backbone and of loop-2 regions from myosins of other species showed actin-activated ATPase activities that correlated well with the activity of the myosins from which the loop sequences were derived [107]. Further studies showed that the initial weak binding of myosin to actin is an electrostatic interaction between positively charged lysine residues in loop 2 and negatively charged residues in subdomain 1 of actin [64,66,101,105,[108][109][110][111]. Removal of the negative charge from subdomain 1 of actin decreases the affinity of actin for myosin in the presence of Mg. ATP, while relocation of the charge in this subdomain does not alter actomyosin function, consistent with limited stereospecificity of the weak binding interaction [110,112].…”
Section: Loopmentioning
confidence: 89%